Eficiência relativa da gestão de saúde nos municípios do Estado do Ceará - Teles, José Sinval (2018)
In Brazil, with the advent of the Federal Constitution of 1988, the Sistema Único de Saúde was implemented, observing the application of new concepts: universality of access, integrality, equality, resolubility and equity of care, decentralization with management, tripartite responsibility, regionalization and hierarchization of the health services network. Therefore, the present study deals with the municipal health management in the State of Ceará, starting from the specificity of Brazilian federalism and the creation of the SUS, with a division of responsibilities between entities in a structured manner in a Management Pact that guides the decentralization of actions and health services, as well as the processes of agreement among the managers of the Union, of the states and municipalities, observing the following planning instruments: Regionalization Master Plan, Investment Master Plan and Integrated Program of Health Care. The general objective of this study was to analyze the relative efficiency of the management of public health services in the municipalities of the state of Ceará, in the year 2015. For that, a descriptive research of a quantitative and documentary nature was carried out. In order to calculate the relative efficiency indices of municipal health management, the non-parametric methodology was used to analyze results-oriented data and with variable returns to scale (DEA-RSV) using the following inputs: public expenditure per capita with health , number of physicians per thousand inhabitants, number of nurses per thousand inhabitants and percentage of revenue applied in actions and public health services. The selected outputs were the Firjan index of municipal development (Health) and the infant mortality rate. According to the results, it was concluded that among the 172 municipalities analyzed, only 25 (14.5%) were considered efficient, and 147 of them (85.5%) were evaluated as inefficient. It was also observed that, among the efficient municipalities, there were predominance of those with up to 50 thousand inhabitants, in number of 17, while the remaining eight municipalities have a population between 50 thousand and 130 thousand inhabitants, but only Iguatu and Maranguape own population of over 100 thousand inhabitants. There has also been a lack of monetary and human resources on the part of the DMUs that are below the efficiency frontier but that there are good margins of productive improvements that can bring them within reach of the efficiency frontier.